2014
DOI: 10.5455/medarh.2014.68.47-50
|View full text |Cite
|
Sign up to set email alerts
|

Post Stroke Depression

Abstract: Introduction:Comorbidity of depression and stroke significantly reduces the quality of life of patients after the stroke. Squeal after stroke also determines the quality of life and have impact on the occurrence of depression after the stroke. In our study we investigated the occurrence of depression in patients after different types and subtypes of stroke measured by the Hamilton scale compared to the level of disability measured by NIHSS scale.Goal:The goal was to make a comparative analysis of depression af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 17 publications
3
47
1
2
Order By: Relevance
“…A total of 66.6% of the stroke patients admitted in the rehabilitation unit had different degrees of depression, in contrast with the PSD frequency of 33-50% in the previous published studies (Alajbegovic et al, 2014;Brown et al, 2012). The high-PSD frequency could be explained by the study patients who were below 60-years-old, and most of them had an active professional status.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…A total of 66.6% of the stroke patients admitted in the rehabilitation unit had different degrees of depression, in contrast with the PSD frequency of 33-50% in the previous published studies (Alajbegovic et al, 2014;Brown et al, 2012). The high-PSD frequency could be explained by the study patients who were below 60-years-old, and most of them had an active professional status.…”
Section: Discussioncontrasting
confidence: 72%
“…The systematic reviews showed that poststroke depression (PSD) may affect between 33% and 50% of stroke survivors (Alajbegovic et al, 2014;Brown et al, 2012), with prevalence peaking approximately 6 months after the vascular event (Dwyer Hollender, 2014;Saarni et al, 2007). When compared with non-depressed stroke patients, PSD is associated with worse long-term outcomes (National Institute for Health and Clinical Excellence, 2009;Prince et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the level of disability, those who survive may at times experience some short periods of grief and sadness during the recovery process. But about one third of patients experience symptoms of longer duration and greater severity, and are diagnosed with post stroke depression (PSD) (Alajbegovic, Djelilovic-Vranic, Nakicevic, Todorovic, & Tiric-Campara, 2014). These statistics make the risk of depression after stroke nearly double that of the general population (Ayerbe, Ayis, Rudd, Heuschmann, & Wolfe, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[14] The other authors like Alajbegovic et al reported post-stroke depression to be more common in females. [15] Lastly the difference in the nature of depression is reported by Paradiso S who in his study found that in men major depression was associated with greater impairment in activities of daily living, and greater severity of depression was associated with greater impairment in daily activities and social functioning while in women, greater severity of depression was associated with prior diagnosis of psychiatric disorder and cognitive impairment. However in context of developing world the studies favor the incidence of depression to be more in male stroke survivors.…”
Section: Discussionmentioning
confidence: 94%